2002
DOI: 10.1071/ea01064
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Prunus necrotic ringspot virus in almond: effect of sampling time on the efficiency of serological and biological indexing methodologies

Abstract: The reliability of enzyme-linked immunosorbent assay (ELISA) and indexing methodologies for the detection of Prunus necrotic ringspot virus (PNRSV) in almond was assessed under local conditions. Thirteen field-grown almond trees were sampled fortnightly throughout the growing season. Petal and leaf homogenates were used for ELISA and to inoculate herbaceous indicator species, while buds collected from October onwards were budded to woody indicators. ELISA reliably detected PNRSV in petals and young leaves from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Assays other than bioassays can provide more rapid detection and identification of known disease agents (Bertozzi et al, 2002;Martin et al, 2002;Lopez et al, 2003Lopez et al, , 2009Singh & Ready, 2003;Rowhani et al, 2005;EPPO, 2006c;Constable et al, 2013). Although the International Plant Protection Convention (IPPC, 2012) and EPPO (EPPO, 2000c(EPPO, , 2004a(EPPO, ,b, 2005(EPPO, , 2006b have indicated that detection of pathogens can be achieved using a biological test, final identification requires either a serological or molecular test.…”
Section: Discussionmentioning
confidence: 99%
“…Assays other than bioassays can provide more rapid detection and identification of known disease agents (Bertozzi et al, 2002;Martin et al, 2002;Lopez et al, 2003Lopez et al, , 2009Singh & Ready, 2003;Rowhani et al, 2005;EPPO, 2006c;Constable et al, 2013). Although the International Plant Protection Convention (IPPC, 2012) and EPPO (EPPO, 2000c(EPPO, , 2004a(EPPO, ,b, 2005(EPPO, , 2006b have indicated that detection of pathogens can be achieved using a biological test, final identification requires either a serological or molecular test.…”
Section: Discussionmentioning
confidence: 99%